Experimental study on a multi-stage air gap membrane distillation (AGMD) unit - Bahar, Rubina; Hawlader, Mohammad Nurul Alam; Ng, K. C.; Yee, Jiun Haw (UTM Press, 2014)
Membrane distillation (MD) is a separation process that involves vapour transport through a hydrophobic membrane. The evaporation is caused by the partial pressure difference between a hot fluid and cold fluid/surface. In this study, an air gap MD (AGMD) process is utilized to produce freshwater from saline solution. A multi-stage AGMD unit with 0.45 micro-m pore size Polyvinylidene Fluoride (PVDF) membranes is built and experiments have been carried out with different operating variables including feed temperature, coolant temperature, air gap width and feed inlet concentration. A maximum of 12.9 kg/m2 of distillate flux was obtained per kWh energy input from the multi-stage MD unit while for a previously built single-stage MD unit, the highest water/power ratio obtained was only 2.3 kg /m2 kWh. This variation indicates that multistaging is necessary for efficient energy use in MD system.